メタボリックシンドロームにおけるプロテアーゼ活性化型受容体２を介した血管弛緩反応の雌雄差及び動脈部位差における検討 - 籠田, 智美; 懐, 理紗; J., McGuire John; 麓, (丸山) 加菜; 篠塚, 和正 (日本薬理学会年会要旨集, 2022)
Activation of protease-activated receptor 2 (PAR2) on vascular endothelial cells causes vasorelaxation. Nitric oxide (NO)-mediated vasorelaxation of the aorta is impaired in male SHRSP.Z-Leprfa/IzmDmcr (SP.ZF) rats with metabolic syndrome (MetS), but PAR2-mediated vasorelaxation is preserved. In the current study, we investigated whether PAR2-mediated vasorelaxation in the thoracic aorta and superior mesenteric artery (MA) differed by sex and arterial site in SP.ZF rats, and SHR.Cg-Leprcp/NDmcr (CP) rats at 23–26 weeks of age, two different models of MetS.Vasorelaxation was examined using the organ bath method. In isolated aortas from SP.ZF rats, vasorelaxations evoked by 2fLIGRLO, a PAR2 agonist, and by acetylcholine (ACh) were greater in females than in males, but in the case of CP rats, only ACh-induced relaxation was greater in females. In MA, 2fLIGRLO-induced vasorelaxation was smaller in females than in males in both strains. However, ACh-induced relaxations did not differ between sexes. Nitroprusside-induced relaxation did not differ significantly between sexes or arterial sites.The findings demonstrate the presence of sex- and arterial site-dependent differences in PAR2-mediated vasorelaxations in MetS. The results indicate less PAR2-mediated relaxation in MAs of female rats under the condition of a presumably maintained NO-mediated vasorelaxation pathway. Further studies are needed to elucidate the pathophysiological significance of lower capacity for vasorelaxation via PAR2 in females with MetS.